Performance and Civic Engagement (Springer International Publishing, 2018)
This book explores 'civic engagement' as a politically active encounter between institutions, individuals and art practices that addresses the public sphere on a civic level across physical and virtual spaces. Taking a multidisciplinary approach, it tracks across the overlapping discourses of politics, cultural geography and performance, investigating how and why physical and digital spaces can be analysed and utilized to develop new art forms that challenge traditional notions of how performance is political and how politics are performative. Across three sections - Politicising Communities, Applying Digital Agency and Performing Landscapes and Identities - the ten chapters and three interviews cover a wide variety of international perspectives, all informed by innovative ways of addressing the current crisis of social fragmentation through performance. Providing access to many debates on the theory and practice of new media, this book is of significance to readers from a broad set of academic disciplines, including politics, sociology, geography, and performance studies.